Hollow particles, method for making the hollow particles, and heat dissipation fluid composition containing the hollow particles
By using hollow spherical particles formed by ceramic particles and conductive carbon-based particles in secondary batteries, combined with insulating oil and thermally conductive fluid, the internal heat control problem of battery modules is solved, and efficient heat dissipation performance and electrical safety are achieved.
Patent Information
- Application Number
- CN202180004186.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2021-01-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-01-26
AI Technical Summary
The existing heat dissipation fluids in secondary batteries have a risk of battery explosion due to high conductivity, and traditional inorganic particles have deteriorated heat dissipation performance, which cannot effectively control the heat inside the battery module.
Using hollow spherical particles containing ceramic particles and conductive carbon-based particles, an inorganic particle layer is formed by acid treatment and heat treatment, and an empty internal space is formed inside it, and a polymer coating is formed by combining insulating oil and thermal fluid. Heat dissipation fluid composition.
It improves the heat dissipation performance, avoids electrical problems inside the battery, and does not settle, maintains excellent heat dissipation performance, and can effectively dissipate heat even after repeated charging and discharging of the battery.
Smart Images

Figure CN114008174B_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2020-0010963, filed on January 30, 2020, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0004] The invention relates to hollow particles capable of improving the heat dissipation performance of heat dissipation fluid, a method for preparing the hollow particles, and a heat dissipation fluid composition containing the hollow particles. Background Art
[0005] Secondary batteries are considered to be the core technology of smart grids capable of storing, charging and discharging large amounts of electricity, including various types of batteries connected in series and / or in parallel. Research to further increase the capacitance of batteries has been actively conducted in various institutions, and batteries with increased capacitance increase the driving range of electric vehicles and enable the use of stored electrical energy in homes and industries, thereby improving the quality of life.
[0006] However, in order to increase the capacitance of the secondary battery, when the power density inside the battery module is increased, heat-related problems caused by high-speed charging and discharging of a large amount of energy arise. Failure to control the heat inside the battery module leads to a rapid decline in battery life and the risk of explosion and fire. Therefore, it is necessary to have excellent heat dissipation characteristics that can quickly discharge the heat inside the battery module to the outside. Although such requirements can be met by an air cooling method that controls heat by driving a fan and passing air in the atmosphere through the battery and discharging it to the outside of the battery module, the air cooling method has disadvantages such as maximizing the module volume due to the inclusion of a fan, generating noise, increasing costs, and power loss due to the need to drive a fan.
[0007] Therefore, as a method to replace the air cooling method, attempts have been made to improve heat dissipation characteristics by immersing the battery with a heat dissipation fluid instead of installing a fan inside a module including the battery.
[0008] However, when a material such as water or ethylene glycol is used as a heat dissipation fluid, there may be a risk of battery explosion or the like because such a fluid has high electrical conductivity, and therefore, the use of an oil-type fluid showing high electrical insulation is considered, and until now, conventional engine oil, gear oil, silicone oil, mineral oil, etc. are known as heat transfer oils. However, these fluids are insufficient in heat dissipation capability to dissipate the heat generated by repeated high-speed charging and discharging of batteries to a satisfactory level.
[0009] Therefore, attempts have been made to add heat-conductive inorganic particles to the heat dissipation fluid to further improve the heat dissipation characteristics, but after a long time, the inorganic particles settle due to the weight of the inorganic particles, resulting in a significant decrease in the heat dissipation characteristics. In addition, carbon-based inorganic particles with high heat dissipation performance, such as graphite particles, carbon nanotubes, and graphene particles, have high electrical conductivity and therefore cannot be used as inorganic particles mixed with the heat dissipation fluid, and although inorganic particles that have only advantages in electrical conductivity but low heat dissipation performance, such as silica and alumina particles, have been used as inorganic particles mixed with the heat dissipation fluid, the heat dissipation performance of silica and alumina particles is somewhat poor.
[0010] Therefore, there is a need to study inorganic particles that can improve heat dissipation performance by mixing with heat dissipation fluid. Summary of the invention
[0011] Technical issues
[0012] The present invention aims to provide hollow particles with excellent heat dissipation performance, a method for preparing the hollow particles, and a heat dissipation fluid composition containing the hollow particles.
[0013] Technical Solution
[0014] One aspect of the present invention provides hollow spherical particles including: an inorganic particle layer including ceramic particles and conductive carbon-based particles; and a polymer coating layer surrounding the inorganic particle layer, wherein an empty internal space is formed inside the inorganic particle layer.
[0015] Another aspect of the present invention provides a method for manufacturing hollow particles according to one embodiment of the present invention, the method comprising: (A) treating spherical particles formed of a thermoplastic polymer with an acid and adding conductive carbon-based particles; (B) immersing the particles of step (A) in a ceramic precursor solution, thereby introducing ceramic precursor ions; (C) heat-treating the particles of step (B), thereby forming an inorganic particle layer including ceramic particles and conductive carbon-based particles on the surface of the particles, and at the same time, forming an empty internal space inside the inorganic particle layer; and (D) immersing the particles of step (C) in a hydrophilic resin solution, thereby forming a polymer coating on the outside of the inorganic particle layer.
[0016] Another aspect of the present invention provides a heat dissipation fluid composition, which comprises: insulating oil; a heat transfer fluid; and hollow particles according to one embodiment of the present invention.
[0017] Beneficial Effects
[0018] According to the present invention, hollow particles can be provided, which contain a carbon-based inorganic material which cannot be mixed with a heat dissipation liquid due to its high electrical conductivity and have excellent heat dissipation performance.
[0019] Furthermore, a method for producing hollow particles by a simple process can be provided.
[0020] Furthermore, a heat dissipation fluid composition having improved heat dissipation performance due to the inclusion of the hollow particles can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a diagram schematically illustrating a method for producing hollow particles according to one embodiment of the present invention.
[0022] Figure 2 is an exploded perspective view of a battery module including a module housing and batteries according to one embodiment of the present invention.
[0023] Figure 3 is a graph schematically illustrating temperature changes of a battery during charge and discharge according to one embodiment. DETAILED DESCRIPTION
[0024] Hereinafter, the present invention will be described in more detail to help understand the present invention. Herein, the terms or words used in this specification and claims should not be understood as limited to the commonly used or dictionary meanings, and, based on the principle that the inventor can correctly define the concept of the term in order to describe his or her invention in the best way, the terms or words should be interpreted with the meaning and concept consistent with the technical concept of the present invention.
[0025] In the present specification, terms such as “comprising,” “including,” or “having” are intended to indicate the presence of implemented features, numbers, steps, components, or a combination thereof, and should be understood as not excluding the possibility of adding or existing one or more other features, numbers, steps, components, or a combination thereof.
[0026] In addition, in this specification, when it is stated that a layer or element is formed “on” or “over” another layer or element, this means that the first layer or element is directly formed on the second layer or element, or a third layer or element may be additionally formed between the above layers, on the object, or on the substrate.
[0027] (Hollow particles)
[0028] The hollow particles of the present invention are hollow spherical particles comprising: an inorganic particle layer including ceramic particles and conductive carbon-based particles; and a polymer coating layer surrounding the inorganic particle layer, wherein an empty internal space is formed inside the inorganic particle layer.
[0029] Since the hollow particles of the present invention include both ceramic particles having advantages in electrical conductivity and conductive carbon-based particles that cannot be mixed with a heat dissipation fluid due to their high electrical conductivity, and include a polymer coating, for example, a polymer coating having a relative dielectric constant of less than 45, hollow particles having excellent heat dissipation performance can be provided. The polymer coating prevents charged particles from being conducted into the heat dissipation fluid through the conductive carbon-based particles, thereby reducing the occurrence of electrical problems inside the battery.
[0030] According to one embodiment of the present invention, the ceramic particles may include one or more selected from the group consisting of silica, alumina, and aluminosilicate.
[0031] According to one embodiment of the present invention, the conductive carbon-based particles may include one or more selected from graphite, graphene, and carbon nanotubes.
[0032] The inorganic particle layer including the ceramic particles and the conductive carbon-based particles may include one or more selected from silicon dioxide, aluminum oxide and aluminosilicate and one or more selected from graphite, graphene and carbon nanotubes. For example, the inorganic particle layer may include aluminum oxide and carbon nanotubes, or may include silicon dioxide and graphene.
[0033] Meanwhile, silicon dioxide may be any silicon dioxide other than fumed silicon dioxide, and aluminum oxide may be any aluminum oxide other than fumed aluminum oxide. Fumed silicon dioxide and fumed aluminum oxide have a large number of pores inside, so the thermal conductivity is not high, and because the size of the pores is small, there is a problem that the heat dissipation fluid cannot penetrate into the large number of internal pores.
[0034] According to one embodiment of the present invention, the weight ratio of the ceramic particles to the conductive carbon-based particles may be in the range of 5: 1 to 3: 1, 5: 1 to 4: 1, or 4: 1 to 3: 1. When the weight ratio of the ceramic particles to the conductive carbon-based particles is within the above range, it is desirable in terms of improving conductivity and heat dissipation performance.
[0035] According to one embodiment of the present invention, the polymer coating may include a polymer having a relative dielectric constant of 45 or less. In this case, problems that may occur in a battery due to the high conductivity of the conductive carbon-based particles inside the polymer coating can be prevented. For example, an electrical short circuit phenomenon that may occur in a battery can be improved.
[0036] Meanwhile, the polymer coating layer may include an adhesive resin layer and a resin layer having a relative dielectric constant of less than 45. That is, the polymer coating layer may include two layers. The adhesive resin layer may be a layer configured to improve the bonding strength between the hollow inorganic particles and the coating layer, and the resin layer having a relative dielectric constant of less than 45 may be a layer configured to improve electrical short circuit phenomenon.
[0037] According to one embodiment of the present invention, the thickness of the polymer coating layer may be 0.3 μm to 2 μm, 0.2 μm to 1.5 μm or 0.1 μm to 1 μm. When the thickness of the polymer coating layer is within the above range, the heat dissipation performance is excellent, and electrical problems that may occur inside the battery due to the conductive carbon-based particles can be prevented.
[0038] According to one embodiment of the present invention, the average particle size (D 50 ) can be 0.5 μm to 5 μm, 0.6 μm to 4 μm or 0.7 μm to 3 μm. When the average particle size of the hollow particles is within the above range, the agglomeration between the particles due to van der Waals force is relatively less serious, that is, the particles are well dispersed, which can be better in improving the heat dissipation characteristics.
[0039] According to one embodiment of the present invention, the hollow diameter of the hollow particles can be 0.1 μm to 2 μm or 0.2 μm to 1.5 μm. When the hollow diameter of the hollow particles is within the above range, it is desirable in terms of improving heat dissipation performance because the particles do not collapse and can maintain a hollow state when a ball mill is used to manufacture a heat dissipation fluid.
[0040] In this specification, the average particle size (D 50 ) and hollow diameter. Specifically, 20 particles were selected using SEM, the particle size and hollow diameter of each of these particles were measured using an icon bar that can be used to measure the diameter, and then the arithmetic mean was calculated.
[0041] (Hollow Particle Manufacturing Method)
[0042] The method for manufacturing hollow particles according to one embodiment of the present invention comprises: (A) treating spherical particles formed of a thermoplastic polymer with an acid and adding conductive carbon-based particles; (B) immersing the particles of step (A) in a ceramic precursor solution, thereby introducing ceramic precursor ions; (C) heat-treating the particles of step (B), thereby forming an inorganic particle layer containing ceramic particles and conductive carbon-based particles on the surface of the particles, and at the same time, forming an empty internal space inside the inorganic particle layer; and (D) immersing the particles of step (C) in a hydrophilic resin solution, thereby forming a polymer coating on the outside of the inorganic particle layer.
[0043] In the following, each step will be described in more detail.
[0044] In step (A), spherical particles formed of a thermoplastic polymer are treated with an acid, and conductive carbon-based particles are added. In step (A), the surface of the spherical particles formed of a thermoplastic polymer is carbonized.
[0045] Since the method of the present invention includes step (A), conductive carbon-based particles that are not easily combined with thermoplastic polymers can be easily formed on the thermoplastic polymer, and a polymer form that can be impregnated with a ceramic particle precursor solution during the subsequent introduction of ceramic particles such as silica, alumina and aluminosilicate particles can be obtained.
[0046] Specifically, in step (A), spherical particles formed of a thermoplastic polymer may be treated with an acid to modify the surface of the particles with anions, and then conductive carbon-based particles, for example, one or more selected from graphite, graphene, and carbon nanotubes may be added, thereby producing spherical particles formed of a thermoplastic polymer and having a carbon-treated surface.
[0047] Figure 1 FIG. 1 is a schematic diagram of a method for producing hollow particles according to an embodiment of the present invention.
[0048] Reference Figure 1 The spherical particles 300 formed of a thermoplastic polymer and having a carbon-treated surface may be manufactured by treating the spherical particles 100 formed of a thermoplastic polymer with an acid to modify the surface of the particles with anions, and then adding conductive carbon-based particles.
[0049] The acid treatment can be performed at a pH of 2 to 5, in which case the interior and surface of the particles can be modified without destroying the thermoplastic polymer due to the diffusion effect. In this case, the degree of introduction of anions into the interior can be adjusted by controlling the stirring time and stirring speed.
[0050] According to one embodiment of the present invention, the thermoplastic polymer can be one or more selected from styrene, poly(styrene-to-divinylbenzene) and polyphenylene ether. When the above-mentioned material is used as the thermoplastic polymer, the thermoplastic polymer can be selectively only removed in the thermal treatment process of step (C) without affecting the hollow inorganic particles.
[0051] In step (B), the particles of step (A) are immersed in a ceramic precursor solution, thereby introducing ceramic precursor ions. That is, spherical particles formed of a thermoplastic polymer and having a carbon-treated surface are immersed in a ceramic precursor solution, for example, a solution containing one or more selected from tetrachlorosilane and aluminum tri-sec-butoxide (ATSB), thereby introducing ceramic precursor ions. The ceramic precursor solution may be a solution containing tetrachlorosilane, a solution containing ATSB, or a solution containing tetrachlorosilane and ATSB in a weight ratio of 1:1.
[0052] Since the method of the present invention includes step (B), hollow inorganic particles including both ceramic particles and conductive carbon-based particles can be easily produced.
[0053] refer to Figure 1 When the spherical particle 300 formed of a thermoplastic polymer and having a carbon-treated surface is immersed in an ATSB solution, aluminum oxide precursor ions, such as Al 3+ ion.
[0054] In step (C), the particles of step (B) are heat-treated, thereby forming an inorganic particle layer containing the ceramic particles and the conductive carbon-based particles on the surface of the particles, and at the same time, forming an empty internal space inside the inorganic particle layer. Specifically, in step (C), hollow inorganic particles are manufactured in which an inorganic particle layer containing ceramic particles and conductive carbon-based particles is formed on the surface of the particles.
[0055] In the present invention, since a simple heat treatment is performed in step (C), ceramic precursor ions react with oxygen, thereby generating one or more selected from silicon dioxide, aluminum oxide and aluminosilicate. Figure 1 , the hollow inorganic particles 500 in which the inorganic particle layer including aluminum oxide and carbon nanotubes is formed can be easily prepared.
[0056] According to one embodiment of the present invention, the heat treatment of step (C) can be carried out at a temperature of 500°C to 1,000°C, 550°C to 950°C or 600°C to 900°C. When the heat treatment temperature of step (C) is in the above range, the hollow inorganic particles can be unaffected, and only the thermoplastic polymer can be selectively removed. The heat treatment of step (C) can be carried out for 1 to 3 hours so as to selectively remove only the thermoplastic polymer.
[0057] According to one embodiment of the present invention, the heat treatment of step (C) can be carried out under oxygen conditions. In this case, the styrene polymer is removed by converting it into carbon dioxide, which has the effect of forming a hollow structure, and since the ceramic precursor ions on the surface are combined with oxygen to produce silicon dioxide or aluminum oxide, hollow inorganic particles with an empty internal space formed inside the inorganic particle layer are obtained.
[0058] In step (D), the particles of step (C) are immersed in a hydrophilic resin solution, and thus a polymer coating layer is formed on the outside of the inorganic particle layer.
[0059] According to one embodiment of the present invention, step (D) may further include a step of immersing the particles of step (C) in a binder resin solution before immersing them in the hydrophilic resin solution.
[0060] Specifically, in step (D), the hollow inorganic particles may be immersed in a binder resin solution, dried, and then immersed in a hydrophilic resin solution, dried, and thereby the polymer coating layer may be formed.
[0061] Reference Figure 1 When, according to step (D), the hollow inorganic particles are immersed in a binder resin solution, dried, and then immersed in a hydrophilic resin solution, and dried, hollow particles 600 in which a polymer coating is formed on the hollow inorganic particles can be obtained.
[0062] According to one embodiment of the present invention, the adhesive resin can be one or more selected from ethylene-vinyl acetate resin, ethylene-methyl acrylate resin, ethylene-acrylic acid resin and cyano resin. In this case, since the adhesion between the hollow inorganic particles and the coating is improved, the coating can be firmly attached to the hollow inorganic particles. That is, the durability of the hollow particles can be improved.
[0063] According to one embodiment of the present invention, the coating resin may be a resin having a relative dielectric constant of 45 or less. For example, the coating resin may be polyvinyl alcohol, polyethylene vinyl alcohol, etc. In this case, electrical problems that may occur in a battery due to the conductivity of the conductive carbon-based particles may be solved.
[0064] (Heat dissipation fluid composition)
[0065] The heat dissipation fluid composition of the present invention comprises: insulating oil; a heat transfer fluid, specifically, a fluid having a relative dielectric constant of 40 or less; and hollow particles according to one embodiment of the present invention.
[0066] According to one embodiment of the present invention, the heat dissipation fluid composition may include 5 to 200 parts by weight of a heat transfer fluid and 5 to 40 parts by weight of hollow particles based on 100 parts by weight of the insulating oil.
[0067] The insulating oil and the heat transfer fluid may form different phases.
[0068] In a heat dissipation fluid composition used in a conventional battery cooling method, inorganic particles are used to improve heat dissipation performance, but there is a problem in that these inorganic particles settle in the composition over time and thus do not contribute to improving heat dissipation performance.
[0069] In order to solve the above problems, the heat dissipation fluid composition of the present invention comprises two liquids that are immiscible and thus form different phases, namely, insulating oil and heat transfer fluid. In the present specification, "insulating oil and heat transfer fluid form different phases" means that the two liquids do not mix with each other and exist as two independent layers, which can be confirmed by the following fact: when the two liquids are mixed, after a period of time, for example, about 5 minutes, more than 90%, or 95% to 100% of the two liquids are separated into separate layers.
[0070] Preferably, the heat transfer fluid is present in the upper layer portion of the heat dissipation fluid composition, and the insulating oil is present in the lower layer portion. Since the hollow particles present in the phase-separated composition do not settle even after a long period of time, the hollow particles contribute to improving the heat dissipation performance regardless of the viscosity of the fluid used. Therefore, the heat dissipation fluid composition can maintain excellent heat dissipation performance even after repeated charging and discharging of the secondary battery, and is therefore suitable for use in a battery module of the secondary battery.
[0071] The heat dissipation fluid composition may further comprise a second fluid miscible with the heat transfer fluid. Here, the fact that the second fluid is miscible with the heat transfer fluid may be confirmed by the fact that when the two fluids are mixed, after a period of time, for example, about 5 minutes, more than 50%, or 80% to 100% of the two fluids do not separate into separate layers, but remain as a single fluid layer.
[0072] As described above, the insulating oil of the present invention combines hollow particles with a fluid and simultaneously forms a separate phase different from the fluid, thereby playing a role in maintaining excellent heat dissipation performance by inhibiting the sedimentation of the hollow particles. As the insulating oil, an oil with high electrical insulation can be used, which does not have electrical conductivity and therefore does not cause dangers such as battery explosion. Therefore, the insulating oil can be a non-polar material with a relative dielectric constant of less than 5.
[0073] Specifically, the insulating oil may be one or more selected from mineral oil, silicone oil and vegetable oil. The mineral oil may be an aliphatic mineral oil or an aromatic mineral oil. In addition, the silicone oil may be a silicone oil having no hydroxyl group at the molecular end. In addition, the vegetable oil may be soybean oil, coconut oil, palm oil, cottonseed oil, camellia oil or hydrogenated oil.
[0074] Preferably, silicone oil or vegetable oil is used as the insulating oil. For example, the insulating oil is soybean oil which has excellent insulating properties and can maintain excellent heat dissipation properties.
[0075] In addition, as the heat transfer fluid of the present invention, a heat transfer fluid that does not cause electrical problems due to a relative dielectric constant value of 40 or less and that exhibits excellent thermal conductivity of 0.10 W / m·K or more, preferably 0.12 W / m·K to 0.3 W / m·K at 20°C can be used.
[0076] Specifically, the relative dielectric constant of the heat transfer fluid can be greater than 15, greater than 10, or greater than 5, and less than 45, less than 40, less than 35, or less than 30. A relative dielectric constant of the heat transfer fluid exceeding 45 does not affect the heat dissipation performance or properties, but in this case, when the component is included in the battery module, electrical problems such as battery explosion may occur. In addition, when the relative dielectric constant of the heat transfer fluid is too low, the fluid cannot form a different phase from the insulating oil, which is undesirable. When the difference in relative dielectric constant between the insulating oil and the heat transfer fluid is, for example, greater than 10, effective phase separation can occur.
[0077] The relative dielectric constant can be measured as the ratio of the dielectric constant of the medium to the dielectric constant of a vacuum using a dielectric constant measuring instrument (Model 871, Sunraytech) under the conditions of a liquid volume of 42 ml and a temperature of 25°C.
[0078] For example, the heat transfer fluid can be ethanol, 2-propanol or 2-methylpropanol (isobutyl alcohol). The relative dielectric constants of ethanol, 2-propanol and 2-methylpropanol measured using a dielectric constant measuring instrument under the above conditions are 24.6, 18.3 and 17.3 respectively, which are suitable for use in heat dissipation fluid compositions.
[0079] In addition, the heat transfer fluid may have a lower density than the insulating oil. For example, the density of the heat transfer fluid at 25° C. may be 0.6 g / mol to 0.85 g / mol, and the density of the insulating oil at 25° C. may be 0.86 g / mol to 0.95 g / mol. Therefore, the heat transfer fluid may be present in the upper layer portion of the heat dissipation fluid composition, and the insulating oil may be present in the lower layer portion.
[0080] Based on 100 parts by weight of insulating oil in the heat dissipation fluid composition, the content of the heat-conducting fluid can be 5 to 200 parts by weight, 5 to 150 parts by weight, or 10 to 100 parts by weight. When the content of the heat-conducting fluid is within the above range, the heat dissipation performance will not decrease, and the hollow particles will not settle.
[0081] Based on 100 parts by weight of insulating oil in the heat dissipation fluid composition, the content of the hollow particles according to one embodiment of the present invention can be 5 to 40 parts by weight or 5 to 30 parts by weight. When the content of the hollow particles is within the above range, the heat dissipation performance will not decrease, and the hollow particles will not settle.
[0082] In addition, as described above, the heat dissipation fluid composition of the present invention may further include a second fluid miscible with the heat transfer fluid. In this specification, when the second fluid is expressed as "miscible with the heat transfer fluid", it means that the second fluid can be mixed with the heat transfer fluid without phase separation with the heat transfer fluid, and at the same time, is immiscible with the insulating oil.
[0083] Therefore, it is preferred that the relative dielectric constant of the second fluid is less than 40 or between 15 and 40, and the difference in Hansen solubility parameter between the second fluid and the heat transfer fluid is 4.5 MPa. 1 / 2 Below, preferably 4Mpa 1 / 2 This is preferred because no electrical problems are caused in this case, and since the second fluid is miscible with the heat transfer fluid, the settling of the hollow particles can be prevented, and since the difference in relative dielectric constant between the second fluid and the insulating oil is 10 or more, the second fluid and the insulating oil can be immiscible.
[0084] Here, the Hansen solubility parameter is a standard for determining miscibility between materials, and is a value calculated in consideration of intermolecular interactions, and can be expressed by a total solubility parameter value (Hildebrand solubility parameter, δ) calculated according to the following formula 1:
[0085] [Formula 1]
[0086]
[0087] In formula 1, δ d is the dispersion component dependent on van der Waals forces, δ p is the polar component associated with the dipole moment, and δ h is the hydrogen bonding component.
[0088] Therefore, it can be determined that when the difference in the Hansen solubility parameter calculated according to Formula 1 is smaller, mixing is easier.
[0089] In addition, the second fluid is a heat transfer fluid and may have a thermal conductivity of 0.10 W / m·K or more, preferably 0.12 W / m·K to 0.3 W / m·K at 20° C. Within the above range, the heat dissipation performance of the heat dissipation fluid composition may be improved to a greater extent.
[0090] For example, acetonitrile, propane-1,2-diol or 1-octanol may be used as the second fluid.
[0091] In addition, based on the insulating oil of 100 weight parts in the heat dissipation fluid composition, the summation of hollow particle and the second fluid can be 10 to 100 weight parts, 10 to 80 weight parts or 10 to 60 weight parts. In the heat dissipation fluid composition, based on the insulating oil of 100 weight parts, the content of the second fluid can be 5 to 50 weight parts. When the content of the second fluid was in the above-mentioned range, due to the tendency of the second fluid mixing with the heat-conducting fluid, the sedimentation of hollow particle was suppressed, therefore excellent heat dissipation performance can be maintained.
[0092] Meanwhile, the dispersion stability of the above heat dissipation fluid composition measured to determine the degree of sedimentation of inorganic particles over time may be 90% or more. Here, the dispersion stability is a value obtained by measuring the maximum height of the sedimented particle layer after a certain amount of the composition is placed in a mass cylinder for 30 days, and expressing it as a percentage of the maximum height of the particle layer measured immediately after the composition is placed in the mass cylinder, preferably 95% or more, more preferably 99% or more, and most preferably 100% or more. Since the sedimentation of inorganic particles is prevented for a long time in the heat dissipation fluid composition having the above dispersion stability range, excellent heat dissipation performance can be maintained even after repeated charging and discharging of the battery.
[0093] (Battery Module)
[0094] Yet another aspect of the present invention provides a battery module including: a module housing; a battery cell installed in the module housing; and a heat dissipation fluid composition according to an embodiment of the present invention filled in the module housing.
[0095] Reference Figure 2 The battery module according to the present invention includes a battery cell inside a module housing and an external plate for electrically connecting the battery cell to an external device (not shown), and, although not shown in the drawings, has a structure in which the heat dissipation fluid composition of the present invention is filled as required to a predetermined height not exceeding 90% of the internal height inside the module housing. In addition, in order to evaluate the heat dissipation performance of the heat dissipation fluid composition, a temperature line may be connected to certain parts of the module housing and the battery so that the temperature inside the module can be measured during charging and discharging.
[0096] In this case, aluminum, plastic, stainless steel, or a combination of two or more thereof can be used as the module housing. For example, polyethylene terephthalate (PET) having excellent heat dissipation performance or aluminum having excellent durability and easy transportation can be used. In addition, the heat dissipation fluid composition can be filled to less than 90% of the total height inside the module housing, or 30% to 80% of the height.
[0097] The maximum voltage of the battery cell may be less than 65 V, or 20 V to 55 V. When the above range is met, electrical problems due to high voltage do not occur.
[0098] (Battery Pack)
[0099] Another aspect of the present invention provides a battery pack, comprising: two or more battery modules according to one embodiment of the present invention; and a packaging shell for accommodating the battery modules. The battery pack of the present invention has excellent internal electrical insulation and quickly dissipates heat that may cause battery explosion. In particular, since the hollow particles of the heat dissipation fluid composition contained in the battery module will not settle even if repeatedly charged and discharged, it is possible to maintain excellent heat dissipation performance.
[0100] The battery pack may include 2 to 30 or 5 to 20 battery modules. When the above range is satisfied, excellent electrical performance and excellent heat generation performance may be exhibited.
[0101] [Invention Mode]
[0102] Hereinafter, exemplary embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in several different forms and is not limited to the embodiments described herein.
[0103] <Examples and Comparative Examples>
[0104] Example 1
[0105] (1) Preparation of hollow particles I
[0106] When the average particle size (D 50 ) were treated with 500 g of sulfuric acid to modify the particle surface with anions, and then 25 g of carbon nanotubes (LG Chem) were added.
[0107] The carbon-treated styrene spherical particles were immersed in 100 ml of ATSB solution to introduce alumina precursor cations (Al 3+ ).
[0108] The spherical particles of styrene treated with carbon and into which aluminum oxide precursor cations were introduced were heat-treated at 800° C. for 1 hour under oxygen conditions, thereby forming an inorganic particle layer containing aluminum oxide and carbon nanotubes in a weight ratio of 4:1 on the surface of the particles, and at the same time, hollow inorganic particles in which an empty internal space was formed inside the inorganic particle layer were obtained.
[0109] The hollow inorganic particles were immersed in a binder resin solution (20% (w / w) cyano resin solution (solvent: acetonitrile), Shinetsu), dried at 100°C, immersed in a coating resin solution (20% (w / w) styrene-butadiene rubber solution (solvent: tetrahydrofuran (THF))), and then dried at 90°C to obtain a polymer coating having a thickness of 0.3 μm and an average particle size (D 50 ) is 1 μm and the hollow diameter is 0.3 μm.
[0110] (2) Preparation of heat dissipation fluid composition
[0111] 100 weight parts of soybean oil (Beksul Soybean Oil, CJ Cheiljedang Corp.) as insulating oil and 50 weight parts of ethanol as heat-conducting fluid were placed in a 1L cylindrical reactor at room temperature, and after about 5 minutes, it was confirmed that soybean oil and ethanol were separated into different phases and formed respective layers, thereby obtaining the first mixture. 30 weight parts of hollow particles 1 and 30 weight parts of acetonitrile (Hansen solubility parameter: 24.4 MPa) as the second fluid were added. 1 / 2 ) was placed in another 1L cylindrical reactor containing 1kg of zirconia balls with a diameter of 1mm, and stirred at 200rpm for 2 hours using a ball mill. After stirring, a second mixture was obtained by filtration, and then mixed with the first mixture to obtain a heat dissipation fluid composition. The obtained heat dissipation fluid composition was separated into different phases to form a heat dissipation fluid composition containing ethanol (density: 0.789g / ml, Hansen solubility parameter: 26.5MPa 1 / 2 ) and a lower layer containing soybean oil (density: 0.917 g / ml).
[0112] Example 2
[0113] Hollow particles II and a heat dissipation fluid composition were prepared in the same manner as in Example 1, except that a tetrachlorosilane solution was used instead of the ATSB solution used in Example 1, and graphene was used instead of the carbon nanotubes.
[0114] Example 3
[0115] Hollow particles III and a heat dissipation fluid composition were prepared in the same manner as in Example 1, except that the hollow inorganic particles were prepared when an inorganic particle layer comprising aluminum oxide and carbon nanotubes in a weight ratio of 3:1 was formed on the surface of the particles instead of forming an inorganic particle layer comprising aluminum oxide and carbon nanotubes in a weight ratio of 4:1 on the surface of the particles as in Example 1.
[0116] Example 4
[0117] Hollow particles IV and a heat dissipation fluid composition were prepared in the same manner as in Example 1, except that a poly(methyl methacrylate) solution was used as the coating resin solution instead of the styrene-butadiene rubber solution used in Example 1 to prepare hollow particles.
[0118] Example 5
[0119] Hollow particles V and heat dissipation fluid compositions were prepared in the same manner as in Example 1, except that a 30% (w / w) poly(ethylene-co-vinyl acetate) solution (solvent: THF) was used as the binding resin solution instead of the 20% (w / w) cyano resin solution used in Example 1 to prepare the hollow particles, and the thickness of the polymer coating was adjusted to 0.4 μm instead of 0.3 μm.
[0120] Example 6
[0121] Except for the preparation of hollow particles, the average particle size (D 50 ) of 2 μm instead of the average particle size (D 50 ) is 1 μm styrene particles, so the average particle size of the hollow particles (D 50 ) was 1.5 μm, hollow particles V and a heat dissipation fluid composition were prepared in the same manner as in Example 1.
[0122] Comparative Example 1
[0123] FR3 (Cargill, Inc.) containing vegetable oil (V-oil) as a main component was used as the heat dissipation fluid composition, and hollow particles, heat transfer fluid, and second fluid were not used.
[0124] Comparative Example 2
[0125] In addition to using the average particle size (D 50 A heat dissipation fluid composition was prepared in the same manner as in Example 1, except that hollow silica particles having a diameter of 1 μm and a hollow diameter of 0.4 μm were used as hollow particles instead of the hollow particles I prepared in Example 1.
[0126] Comparative Example 3
[0127] A heat dissipation fluid composition was prepared in the same manner as in Example 1, except that single-walled carbon nanotubes (791490, Sigma-Aldrich) were used instead of the hollow particles I prepared in Example 1.
[0128] Comparative Example 4
[0129] In addition to using the average particle size (D 50) is 1 μm, the hollow diameter is 0.3 μm, and the hollow inorganic particles of Example 1 without a polymer coating are used as hollow particles instead of the hollow particles I prepared in Example 1. A heat dissipation fluid composition is prepared in the same manner as in Example 1.
[0130] Comparative Example 5
[0131] When the average particle size (D 50 After treating spherical particles of styrene with a diameter of 1 μm with 500 g of sulfuric acid to modify the particle surface with anions, the particles were immersed in 100 ml of ATSB solution to introduce aluminum oxide precursor cations (Al 3 + ).
[0132] The spherical styrene particles into which the aluminum oxide precursor cations were introduced were heat treated at 800° C. for 1 hour under oxygen conditions, thereby forming an inorganic particle layer containing aluminum oxide on the surface of the particles and simultaneously, obtaining inorganic particles having an empty internal space formed inside the inorganic particle layer.
[0133] The hollow inorganic particles were immersed in a binder resin solution (20% (w / w) cyano resin solution (solvent: acetonitrile), Shinetsu), dried at 100°C, immersed in a coating resin solution (20% (w / w) styrene-butadiene rubber solution (solvent: THF)), and then dried at 90°C to obtain a polymer coating having a thickness of 0.3 μm and an average particle size (D 50 ) is 1 μm and the hollow diameter is 0.3 μm.
[0134] A heat-dissipating fluid composition was prepared in the same manner as in Example 1, except that hollow particles VII were used as hollow particles instead of hollow particles I prepared in Example 1.
[0135] Comparative Example 6
[0136] 25 g of carbon nanotubes (LG Chem) were added to 100 g of 50 ) is spherical particles of styrene with a size of 1 μm.
[0137] The carbon-treated styrene spherical particles were heat-treated at 800° C. for 1 hour under oxygen conditions, thereby forming a carbon nanotube layer on the surface of the particles, thereby obtaining particles having an empty internal space formed inside the carbon nanotube layer.
[0138] The particles were immersed in a binder resin solution (20% (w / w) cyano resin solution (solvent: acetonitrile), Shinetsu) without a drying process, and then immersed in a coating resin solution (20% (w / w) styrene-butadiene rubber solution (solvent: THF)) and then dried at 90°C to obtain a polymer coating having a thickness of 0.3 μm and an average particle size (D 50 ) is 1 μm and the hollow diameter is 0.3 μm.
[0139] A heat-dissipating fluid composition was prepared in the same manner as in Example 1, except that hollow particles VIII were used as hollow particles instead of hollow particles I prepared in Example 1.
[0140] <Experimental example>
[0141] The heat dissipation performance and dispersion stability of the heat dissipation fluid compositions prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were measured by the following methods, and the results are shown in Table 1.
[0142] Measurement of heat dissipation performance
[0143] like Figure 2 As shown, after connecting the temperature line to the inside of the battery module housing and the battery cell, the prepared heat dissipation fluid composition was filled to 80% of the internal height of the module housing. Subsequently, while recording the internal temperature of the battery module, the battery cell was charged at a constant current for 0.5 hours at 25°C until the voltage reached 50V, and after standing for 2 hours, the battery cell was discharged at a constant current for 0.5 hours until the voltage reached 50V. The maximum internal temperature (°C) measured by the battery module is shown in Table 1.
[0144] In addition, after the prepared heat dissipation fluid composition was filled to 30% of the inner height of the module housing, the battery cells were charged and discharged in the same manner, and the maximum inner temperature (° C.) of the battery module was shown in Table 1.
[0145] The temperature changes inside the battery cells during the charging and discharging process of the battery module are schematically shown in Figure 3 In. Reference Figure 3, it can be seen that the battery cell heats up during the charging process and reaches the maximum charging temperature, then cools down during the rest period when no charging or discharging occurs, and heats up again during the discharge process, reaching the maximum discharge temperature after a certain period of time. Therefore, by measuring the maximum temperature inside the battery cell, such as the maximum charging temperature and the maximum discharge temperature, it can be determined whether the heat dissipation fluid composition quickly dissipates the heat generated by the battery during the charging and discharging process. The lower the maximum temperature inside the battery module, the more battery cells can be installed in the module, and accordingly, the higher the possibility of increasing the battery capacity. Therefore, in this experimental example, the heat dissipation characteristics were evaluated by measuring the maximum discharge temperature.
[0146] Evaluation of dispersion stability (%)
[0147] 150 g of the prepared heat dissipation fluid composition was put into a measuring cylinder, and the maximum height of the particle layer was designated as 100. After 30 days, the maximum height of the settled particle layer was measured, and the measured value was expressed as a percentage of the initial maximum height.
[0148] [Table 1]
[0149]
[0150]
[0151]
[0152] Referring to Table 1, it can be seen that the battery module using the embodiment of the heat dissipation fluid composition of the present invention has significantly improved heat dissipation performance compared to the battery module of Comparative Example 1 using a conventional heat dissipation fluid.
[0153] At the same time, it can be seen that in the case of the battery module of Comparative Example 2, since the hollow silica particles without conductive carbon-based particles in the inorganic particle layer and without polymer coating around the inorganic particle layer are used as hollow particles, compared with the battery module of the embodiment of the heat dissipation fluid composition of the present invention, the heat dissipation performance and low dispersion stability are shown. In addition, it can be seen that in the case of the battery modules of Comparative Examples 3 and 4, since only single-walled carbon nanotubes are used as hollow particles (Comparative Example 3) or hollow inorganic particles without polymer coating surrounding the inorganic particle layer (Comparative Example 4), compared with the battery module of the embodiment of the heat dissipation fluid composition of the present invention, significantly reduced heat dissipation performance and significantly low dispersion stability are shown, as can be confirmed by the occurrence of electrical short circuit phenomenon. It can be seen that in the case of the battery module of Comparative Example 5, since carbon nanotubes with high thermal conductivity are not used, reduced heat dissipation performance is shown. It can be seen that in the case of the battery module of Comparative Example 6, since carbon nanotubes are not added to ceramic particles, high conductivity is shown, and thus electrical short circuit phenomenon occurs.
[0154] Therefore, it can be seen that according to the present invention, since hollow spherical particles including an inorganic particle layer containing ceramic particles and conductive carbon-based particles and a polymer coating layer surrounding the inorganic particle layer and in which a hollow internal space is formed inside the inorganic particle layer are contained in the heat dissipation fluid composition, both heat dissipation performance and dispersion stability are improved.
[0155] Reference numerals
[0156] 100: Spherical particles formed from thermoplastic polymers
[0157] 200: Spherical particles formed of thermoplastic polymers with anionic surface modification
[0158] 300: Spherical particles formed from thermoplastic polymers and having a carbon-treated surface
[0159] 400: Composed of thermoplastic polymer with Al added to the surface 3+ Spherical particles treated with carbon
[0160] 500: Hollow inorganic particles containing alumina and carbon nanotubes
[0161] 600: hollow inorganic particles comprising alumina and carbon nanotubes; and hollow particles comprising a polymer coating
Claims
1. Hollow particles having a spherical shape, comprising: an inorganic particle layer comprising ceramic particles and conductive carbon-based particles; as well as a polymer coating surrounding the inorganic particle layer, Wherein, the ceramic particles are selected from one or more of silicon dioxide and aluminum oxide, Wherein, the conductive carbon-based particles are selected from one or more of graphene and carbon nanotubes, wherein an empty internal space is formed inside the inorganic particle layer, Wherein, the polymer coating is selected from one or more of styrene-butadiene rubber and poly(methyl methacrylate).
2. The hollow particles according to claim 1, wherein A weight ratio of the ceramic particles to the conductive carbon-based particles is in a range of 5:1 to 3:
1.
3. The hollow particles according to claim 1, wherein The polymer coating has a thickness of 0.3 μm to 2 μm.
4. The hollow particles according to claim 1 have an average particle size D of 0.5 μm to 5 μm. 50 and a hollow diameter of 0.1 μm to 2 μm.
5. A method for producing the hollow particles according to claim 1, comprising: (A) treating spherical particles formed of a thermoplastic polymer with an acid and adding conductive carbon-based particles; (B) immersing the particles of step (A) into a ceramic precursor solution to thereby introduce ceramic precursor ions; (C) heat-treating the particles of step (B), thereby forming an inorganic particle layer including the ceramic particles and the conductive carbon-based particles on the surface of the particles, and at the same time, forming an empty internal space inside the inorganic particle layer; and (D) Immersing the particles of step (C) in a hydrophilic resin solution, thereby forming a polymer coating layer on the outside of the inorganic particle layer.
6. The method according to claim 5, wherein: The thermoplastic polymer is one or more selected from styrene, poly(styrene-co-divinylbenzene) and polyphenylene ether.
7. The method according to claim 5, wherein: In step (C), the heat treatment is performed at a temperature of 500°C to 1,000°C.
8. The method according to claim 5, wherein: In step (C), the heat treatment is performed under oxygen conditions.
9. The method according to claim 5, wherein: Step (D) further comprises immersing the particles of step (C) in a binder resin solution prior to immersing in the hydrophilic resin solution.
10. The method according to claim 9, wherein: The adhesive resin is one or more selected from ethylene-vinyl acetate resin, ethylene-methyl acrylate resin, ethylene-acrylic acid resin and cyano resin.
11. A heat dissipation fluid composition, comprising: Insulating oil; heat transfer fluid; and The hollow particles according to claim 1.
12. The heat dissipation fluid composition according to claim 11, comprising: based on 100 parts by weight of the insulating oil: 5 to 200 parts by weight of the thermally conductive fluid; and 5 to 40 parts by weight of the hollow particles.
Citation Information
Patent Citations
Vertical garden equipment for vertical wall recording
KR1020200010963A
Preparation method of fin structure with heat-conductive adhesive composition
KR101551366B1
Thermally conductive materials based on thermally conductive hollow particles and fabrication method thereof
KR1020130041554A